2013
DOI: 10.1007/s10439-013-0904-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemitry: A Molecular Biomechanics View of Mechanosensing

Abstract: Molecular biomechanics includes two themes: the study of mechanical aspects of biomolecules and the study of molecular biology of the cell using mechanical tools. The two themes are interconnected for obvious reasons. The present review focuses on one of the interconnected areas – the mechanical regulation of molecular interaction and conformational change. Recent conceptual developments are summarized, including catch bonds, regulation of molecular interaction by the history of force application, and cyclic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 115 publications
(164 reference statements)
1
20
1
Order By: Relevance
“…3e-i). Unlike previously described catch bond or cooperative binding cofactors 33,58 , such as allosteric regulation by neighbouring protein domains (that is, within the molecule) or soluble co-factors, our finding is distinct: the co-factor is a nearby co-receptor but not covalently associated with the first. Importantly, as circulating tumour cells are exposed to a complex haemodynamic environment during the their transit through the vasculature 59 , forces applied to non-covalent interactions between adhesion receptors are important perturbations that may regulate bond affinities and subsequent signalling.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…3e-i). Unlike previously described catch bond or cooperative binding cofactors 33,58 , such as allosteric regulation by neighbouring protein domains (that is, within the molecule) or soluble co-factors, our finding is distinct: the co-factor is a nearby co-receptor but not covalently associated with the first. Importantly, as circulating tumour cells are exposed to a complex haemodynamic environment during the their transit through the vasculature 59 , forces applied to non-covalent interactions between adhesion receptors are important perturbations that may regulate bond affinities and subsequent signalling.…”
Section: Discussioncontrasting
confidence: 80%
“…Singlemolecule approaches (that is, the biomembrane force probe (BFP)) have been extensively used to study force regulation of protein-protein interactions, determine protein conformational changes and understand signal initiation [28][29][30][31] , dissecting the relative contribution of individual proteins from complex molecular cohorts 32 . For example, single-molecule studies have elucidated the catch bond behaviour-bonds can be stabilized rather than disrupted by force 33,34 . Catch bonds are probably essential to key cell physiological events that occur in conditions where forces are externally applied or internally generated by the cell, such as adhesion enhancement of circulating cells and bacteria under shear stress or during receptor mechanosignalling [35][36][37] .…”
mentioning
confidence: 99%
“…Catch bond, a counterintuitive behavior where force strengthens the molecular interaction as opposed to slip bond that weakens it, has been suggested to provide a potential mechanosensing mechanism (9, 35, 36). We found that increasing approach/retraction speed by shortening the approach/retraction segments of the contact cycle triggered lower level of calcium in T cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bell's 1978 paper is generally taken as the seminal starting point, although occasionally earlier work by Zhurkov and Eyring is cited. Mechanochemistry is now being applied to a wide range of areas of chemistry and biochemistry, including solvent free synthesis routes [108,111], molecular motors [112,113], single molecule studies, for example using molecular tweezers or AFMs [114,115], cell differentiation [116,117], and mechanophores [118,119]. The latter are molecular groups designed specifically to respond to mechanical force, to enable this force to be measured externally (sensors) or to produce materials that respond in desired ways to applied forces (smart materials).…”
Section: If Dry Chloride Of Silver In Powder Be Triturated In a Mortamentioning
confidence: 99%